2020
DOI: 10.1093/ofid/ofaa536
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Infection Diagnoses and Access to a Sexual Health Service Before and After the National Lockdown for COVID-19 in Melbourne, Australia

Abstract: Background We aimed to examine the impact of lockdown on sexually transmitted infection (STI) diagnoses and access to a public sexual health service in the COVID-19 pandemic in Melbourne, Australia. Methods The operating hours of Melbourne Sexual Health Centre (MSHC) remained the same during the lockdown. We examined the number of consultations and STI at MSHC between January and June 2020 and stratified the data into pre-loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
94
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(106 citation statements)
references
References 21 publications
7
94
0
5
Order By: Relevance
“… 3 , 18 The reduction in sexual risk can potentially lead to temporal reductions in HIV and other sexually transmitted infections (STI). 5 , 19 , 20 However, the severity of COVID-19 pandemic in some settings may cause interruptions in delaying and accessing HIV/STI testing. 21 23 This is supported by a study conducted in 3 Kenyan counties showing that there was a significant reduction in the number of HIV tests at clinical sites during lockdown although there was an increase in HIV self-testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 18 The reduction in sexual risk can potentially lead to temporal reductions in HIV and other sexually transmitted infections (STI). 5 , 19 , 20 However, the severity of COVID-19 pandemic in some settings may cause interruptions in delaying and accessing HIV/STI testing. 21 23 This is supported by a study conducted in 3 Kenyan counties showing that there was a significant reduction in the number of HIV tests at clinical sites during lockdown although there was an increase in HIV self-testing.…”
Section: Discussionmentioning
confidence: 99%
“…Under the previous restrictions during the national lockdown in March and April 2020, individuals had reduced their sexual activities, particularly sex with casual partners. 3 5 There have been a few Australian and international studies examining pre-exposure prophylaxis (PrEP) use during the COVID-19 pandemic. 6 – 8 Our previous Melbourne-based study reported that one in 4 men who have sex with men (MSM) taking daily HIV PrEP in January–February 2020 (ie, before first lockdown) had stopped taking PrEP in early May.…”
Section: Introductionmentioning
confidence: 99%
“…This outcome was probably related to the Spanish government’s decision to minimise all healthcare activities that were not dedicated to COVID-19 in primary care centres, such as STI clinics. As other authors have reported, this led to a reduction in the number of consultations [ 6 ] and in testing volume [ 7 ], since only patients with LGV symptoms were able to access the centres. In fact, a similar drop has been reported for a wide range of communicable diseases [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data could explain the significant increase in the number of LGV cases and the proportion with respect to the CT-positive samples following the first wave. Nonetheless, the resumption of social gatherings, including sexual activities, together with an increase in the asymptomatic screening in the re-opened STI centres [ 6 ] might also have led to the subsequent increase in LGV cases after the lockdown. However, the clinical activity in our centre increased progressively and, now in 2021, has reached the same levels as in the pre-pandemic period.…”
Section: Discussionmentioning
confidence: 99%
“…These restrictions may reduce the opportunity for sex with casual partners and, hence, reduce an individual's sexual risk. 1 , 2 This proposition is supported by substantial declines in presentations for HIV postexposure prophylaxis prescriptions during the COVID-19 lockdowns in several countries such as Australia and the United Kingdom. 3 , 4 We described the impact these restrictions may have had on HIV testing and diagnoses.…”
mentioning
confidence: 96%